BENTUK ANCAMAN DALAM EXPORT RESTRAINT POLICY AUSTRALIA TERHADAP KEAMANAN EKONOMI - Rama, Kadek Atma; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT Australia is the seventh biggest cattle exporters in the world. It is estimated that around 60% of the cattle exported are directed to Australia’s nearest neighbor. However, according to the investigation of violations of the Australian cattle management standards in Indonesia, Australia was forced to temporarily suspend the export in 2011. Instead of providing a deterrent effect against abattoirs in Indonesia, the policy became a domestic loss for Australia, primarily the cattle producers. This study aims to describe the threat of the cattle export restraint policy in 2011 on the economic security, especially for the cattle producers in Australia. This study will be assessed by using the Economic Security, Galtung’s Violence Concepts, and theoretical approach by group in creating the public policy. Keywords: Cattle, Australia, Structural Violence, Economic Security